Topographic and anatomical features of the most important perforating veins of the lower extremities - I. N. Shanaev (Вестник хирургии имени И.И. Грекова)
The objective of the study is to clarify the topographic and anatomical features of the most common perforating veins of the lower extremities.Material and methods. 70 lower extremities (sectional material) without signs of chronic venous diseases and 1700 patients. Research methods: anatomical dissection and ultrasound examination of the venous system of the lower extremities (duplex ultrasound scanning).Results. 4 to 6 perforants were found on the medial surface of the foot. They directly connected the medial boundary of the vein and vv. plantaris medialis. They are located along the medial intermuscular septum at the subfascial level; have subcutaneous tributaries from the medial surface of the foot at the epifascial level. The most constant localization of perforating veins on the ankle was the distal part of the medial surface of the ankle. On the ana to mic preparations they were the main draining vessels of this area. All perforating veins of the ankle (direct and indirect) and foot are the part of the neurovascular bundle, and at the subfascial level of the perforating veins 2, are located on the sides of the artery, next to the nerve branch. Rare incidence of perforating veins of the popliteal region, combining with the lack of typical saphenopopliteal anastomosis, allows relating them to the atypical PV. Among all of the perforating veins of the thigh, the highest frequency of incidence was in the lower third. These veins connected the great saphenous vein, and the femoral vein in 55.6 %. They passed along the medial intermuscular septum and had a long subfascial course. In all cases there is nearby arterial twig.Conclusion. Perforating veins in different areas of the lower extremities have their features of structure. General is that perforating veins mostly are the neurovascular bundles (vein – artery – nerve).